Formation-containment control for multi-robot systems with two-layer leaders via hierarchical controller–estimator algorithms. Issue 12 (August 2018) - Yao, Xiang-Yu; Ding, Hua-Feng; Ge, Ming-Feng
Abstract: This paper studies the formation-containment control for multi-robot systems with two-layer leaders in the presence of parametric uncertainties, input disturbances and directed interaction topologies. To cope with the aforementioned issues, we establish a novel formation-containment control framework, where the analysis of the systems is carried out step by step. A hierarchical controller–estimator (HCE) algorithm, containing distributed sliding-mode estimators in each sub-algorithm, is proposed for the two-layer leaders system. Moreover, by invoking finite-time stable and input-to-state stable theories, the sufficient conditions for convergence of the proposed HCE algorithm are presented. Finally, numerous simulations are performed to demonstrate the validity of the theoretical results.